Identification of characteristics of didactic and meta-didactic mathematical knowledge of novice and expert teachers when reflecting on class episodes - Morales-López, Yuri (2023)
This article describes the didactic analysis carried out by an expert teacher and a novice teacher, based on the didactic suitability criteria (DSC) of the Onto Semiotic Approach (OSA) when analyzing episodes of a high school mathematics class in Costa Rica. This is a qualitative investigation with an interpretive hermeneutic approach. First, a questionnaire was applied to the two participants, to classify them as novice and expert, based on certain defined characteristics. Both teachers then analyzed three video segments using a guide for didactic analysis and, finally, an interview was conducted to elaborate on the reflections previously obtained. The data analysis focused on identification, classification, and comparison of elements in each of the video segments with reference to the OSA’s DSC indicators. The results show that there are differences and similarities between the didactic analysis carried out by these teachers. It is concluded that the novice teacher provides a more descriptive analysis, in which errors are not specified, and focuses on the activities carried out by his students, while the expert teacher, who provides a thoughtful evaluative analysis of, identifying errors in the concepts and focusing his analysis on the teacher’s actions and performance in the video segments.